EVALUATION OF PHYSICAL QUALITY OF BOILED LAYER CHICKEN MEAT USING PAPAYA FRUIT - Hasanah, Ussuwatun; Risdawati Br Ginting; Warisman, Warisman (Journal of Innovation Research and Knowledge, 2024)
Fungal growth is influenced by various additional nutrients given, including the addition of quicklime and palm sap water extract. The purpose of the study was to determine the physical quality of layer chicken meat boiled using young papaya. The study was conducted in June 2024 at the Laboratory of the Panca Budi Development University, Medan, Jl. Gatot Subroto Medan. The research method used a non-factorial Completely Randomized Design (CRD) consisting of 4 treatments and 3 replications. The factors studied were: P0: 1000 grams of chicken meat + 0 grams of papaya, P1 = 1000 grams of chicken meat + 250 grams of papaya, P2 = 1000 grams of chicken meat + 500 grams of papaya and P3 = 1000 grams of chicken meat + 750 grams of papaya. The parameters observed were organoleptic tests (aroma, taste, color, texture, preference). The results of the study showed that boiling layer chicken meat using young papaya had no significant effect on the organoleptic test (aroma, taste, color, texture and preference).